Prevalence and factors associated with shoulder pain in the general population: a cross-sectional study - Thiago Paulo Frascareli Bento; Caio Vitor dos Santos Genebra; Guilherme Porfírio Cornélio; Rangel Dal Bello Biancon; Sandra Fiorelli Almeida Penteado Simeão; Alberto De Vitta (Universidade de São Paulo, 2019)
ABSTRACT Musculoskeletal pain in the shoulder is considered one of the most prevalent causes of pain and disability in adults. To verify the prevalence of shoulder pain and correlated factors in adults aged 20 years or older in cross-sectional study with 600 individuals interviewed through questionnaires: (1) participants characterization; (2) level of physical activity; (3) reported morbidities; and (4) musculoskeletal symptoms. Descriptive, bivariate, and Poisson regression analyses were performed. The prevalence of pain in the shoulder was 24% (CI 20.3%-27.5%). Being 60 years or older (PR=2.14; 1.33-2.45), female (PR=1.92; 1.29-285), using the computer more than three times a week (PR=1.55; 1.01-2.32), working in a sitting position (PR=1.64; 1.03-2.59), standing up leaning the body forward (PR=1.54; 1.00-2.37), and reporting two or more morbidities (PR=3.31; 1.97-5.57) were all indicators of shoulder pain. This study discloses a high prevalence of shoulder pain and a strong relation with women, age, those who use the computer more than three times a week, those who execute occupational activities sitting and standing up leaning the body forward, and those who report two or more diseases.